1973
DOI: 10.1037/h0034872
|View full text |Cite
|
Sign up to set email alerts
|

Memory impairment on the ascending and descending limbs of the blood alcohol curve.

Abstract: The effects of alcohol on memory were investigated using a free-recall verbal memory task. Twenty alcohol subjects were tested before alcohol (base line) and also on the ascending and descending limbs of the blood alcohol curve at a blood alcohol level of .09%. Twenty placebo subjects were tested at three comparable times. Alcohol impaired immediate, short-term, and long-term memory for words presented during the alcohol state. However, there was no effect of alcohol on recall of base-line words either during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
3

Year Published

1980
1980
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(63 citation statements)
references
References 20 publications
2
58
3
Order By: Relevance
“…It is difficult to imagine how some drug (e.g., alcohol, diazepam, atropine) could selectively make one or the other endpoint nondistinctive (see, e.g., Castro, 1995Castro, ,1997Jones, 1973).…”
Section: Distinctiveness As An Alternative Framework For the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to imagine how some drug (e.g., alcohol, diazepam, atropine) could selectively make one or the other endpoint nondistinctive (see, e.g., Castro, 1995Castro, ,1997Jones, 1973).…”
Section: Distinctiveness As An Alternative Framework For the Resultsmentioning
confidence: 99%
“…One focus of the vast amount of research conducted on list memory has been on selective elimination of either the primacy or the recency effect. For example, the recency effect can be selectively eliminated by delaying the test (see, e.g., Glanzer & Cunitz, 1966), whereas the primacy effect can be selectively eliminated with alcohol (see, e.g., Jones, 1973). An implication ofsuch dissociations is that the serial position function is composed ofdifferent underlying memory processes or mechanisms.…”
Section: Rationale For Testing Monkey List Memorymentioning
confidence: 99%
“…Generally, laboratory studies-almost all of which employ alcohol doses that result in an estimated BAC of 0.08% or less-show that alcohol can have a negative effect on episodic memory (e.g., Parker et al, 1976;Ray & Bates, 2006;Hashtoudi et al, 1984;Jones, 1973;Soderlund et al, 2007). However, several studies have not found significant alcohol effects on memory (e.g., Mintzer, Allen & Griffiths, 2001;Saults, Cowan, Sher, & Moreno, 2007;Wetherill & Fromme, 2011;Colflesh & Wiley, 2013;Knowles & Duka, 2004;Moulton et al, 2005), so additional research seems warranted.…”
mentioning
confidence: 99%
“…In three additional studies involving alcohol (Birnbaum, Parker, Hartley, & Noble, 1978;Jones, 1973;Miller et al, 1978, Experiment 1), the experimental designs employed prohibit one from drawing any firm conclusions about the presence or absence of state-{fependent effects.…”
mentioning
confidence: 99%